Building Quality of Democracy and Democratization of Political Partyâ€™s Leader Election - Sulardi, Sulardi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Political parties are crucial assets of democracy. Political parties have strategic functions and roles in building democracy of a country. To create democracy and democratization, thus, the first subject who must practice democratization should be the political parties themselves.Â Until today, Indonesia is still in the process of seeking and progressing towards the ideal form of democratic living (democratization), as envisioned in the constitution. Surely, â€œthe process of democratizationâ€ must be done in all aspects. Democratization in political parties has not been built well, as there are still some political parties whose election of leaders are still influenced by the partiesâ€™ founder and family ties. Building quality of democracy may be initiated by the democratization of political parties, in this case through making better the election mechanism of the leader of the political party. This election process may be done democratically if: there are regulations which have been prepared from the beginning which guarantees the democratic changing process of the political partyâ€™s leader. There should be no â€œfamilialâ€ characteristics in the political parties which will actually create political party dynasties. There should also be a clear limitations regarding the head of the political partiesâ€™ term of office and a more transparent and accountable election of political partyâ€™s election of leader. Â